Influence of teachers in the implementation of the Internet for scientific research and everyday use of Internet by University alumni (Experimental investigation on the case with students from the School of Communication Sciences) - Alcocer-Tinajero, Ma. Isabel (Universidad Autónoma de Tamaulipas, 2010)
The use of Internet to carry out scientific research is almost unknown for college students, therefore it is necessary to guide, apply constant motivation from the teacher to stimulate the process. The application of Internet to download information from specialized libraries and sites of scientific journals as Dianetl Redalyc is an activity that must be taught by teachers for students interested in seeking scientific information online to fulfill their tasks and participate in discussions with scientific arguments. The objective of this article is to investigate how to implement this practice.